Walter Brogan (2005). Heidegger and Aristotle: The Twofoldness of Being. Albany: Published by State University of New York. - Fleig, Mario; Viero, Cristóvão Atílio (Natureza Humana - Revista Internacional de Filosofia e Psicanálise, 2009)